Environmental Care Action: Coastal Clean-Up And Ecosystem Rehabilitation Through Bakau (Mangrove) Seedling Planting At Cibery Beach, Jayapura City: Aksi Lingkungan: Pembersihan Sampah Dan Rehabilitasi Ekosistem Pantai Melalui Penanaman Bibit Bakau Di Pantai Cibery Kota Jayapura - Rahman Rahman; Noper Tulak; Octolia Togibasa; Yane O. Ansanay; Sony Wardoyo; Ego Srivajawaty Sinaga; Sudarmono Sudarmono; Benny A. Bungasalu; Kezia N. Anou; Martina Bunga’; Tatang Sutarman; Khaeriah Dahlan (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
The degradation of coastal ecosystems due to waste accumulation and the decline of mangrove vegetation has become an increasingly significant environmental challenge in the coastal areas of Jayapura City. This community service program aimed to improve the environmental quality of Cibery Beach through an integrated action consisting of coastal clean-up activities, underwater waste collection through diving, and ecosystem rehabilitation by planting mangrove (bakau) seedlings, conducted in commemoration of the 28th Anniversary of the Faculty of Mathematics and Natural Sciences, Universitas Cenderawasih. The implementation employed a participatory approach based on Participatory Action Research (PAR) and service learning, involving lecturers, students, local communities, and environmental volunteers. The activity stages included site assessment, environmental education on coastal conservation, coastal and underwater waste removal, mangrove seedling planting, and initial post-planting monitoring. The results demonstrated a reduction in waste accumulation along the coastline and underwater areas, as well as the stable establishment of mangrove seedlings as an initial step toward ecosystem rehabilitation. Ecologically, the program has the potential to support shoreline stabilization and improve coastal habitat quality, while socially enhancing environmental awareness and community participation in conservation efforts. This integrated action model is recommended as a sustainable approach to collaborative coastal ecosystem management between universities and local communities.